European Bank Deleveraging : Implications for Emerging Market Countries - Feyen, Erik; Kibuuka, Katie; Ötker-Robe, Inci (World Bank, Washington, DC, 2012)
Just before the 2008-9 global financial crises, policy makers were concerned about the rapid growth of bank credit, particularly in Europe; now, worry centers on a potential global credit crunch led by European banking institutions. While recognizing that concrete evidence is limited by significant data gaps and lags, this note discusses the dynamics of European bank deleveraging and possible implications for emerging market economies (EMEs). Overall, the information available as of early 2012 shows a marked deterioration of credit conditions across Europe. Data also suggest that spillover effects are already being felt around the globe and imply significant channels through which deleveraging could have disruptive short and long-term consequences for credit conditions in EMEs, particularly in Central and Eastern Europe (CEE). However, the significant liquidity support provided by the European Central Bank (ECB) since December may be a 'game changer,' at least in the short term, because it has helped revive markets and limited the risk of disorderly deleveraging. The extent, speed, and impact of European bank deleveraging will henceforth depend largely on the evolution of market conditions, which in turn are guided by the ultimate impact of ECB liquidity support, attainment of sovereign debt sustainability and fiscal convergence within the euro zone, and credibility of the European rescue fund as an effective firewall against contagion.